2010
DOI: 10.1093/brain/awp323
|View full text |Cite
|
Sign up to set email alerts
|

Oculopalatal tremor explained by a model of inferior olivary hypertrophy and cerebellar plasticity

Abstract: The inferior olivary nuclei clearly play a role in creating oculopalatal tremor, but the exact mechanism is unknown. Oculopalatal tremor develops some time after a lesion in the brain that interrupts inhibition of the inferior olive by the deep cerebellar nuclei. Over time the inferior olive gradually becomes hypertrophic and its neurons enlarge developing abnormal soma-somatic gap junctions. However, results from several experimental studies have confounded the issue because they seem inconsistent with a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
149
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(159 citation statements)
references
References 60 publications
7
149
1
2
Order By: Relevance
“…We found that the waveform and the frequency of the nystagmus in OPT was more variable and less sinusoidal than in patients with MS. While these observations have already been reported in patients with either APN due to OPT 11,22 or MS, 15,19 by comparing the 2 patient groups in the same study we show that this feature may be important for establishing a differential diagnosis between MS and OPT.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…We found that the waveform and the frequency of the nystagmus in OPT was more variable and less sinusoidal than in patients with MS. While these observations have already been reported in patients with either APN due to OPT 11,22 or MS, 15,19 by comparing the 2 patient groups in the same study we show that this feature may be important for establishing a differential diagnosis between MS and OPT.…”
Section: Resultssupporting
confidence: 72%
“…19 The more influential model of OPT suggests a dual mechanism involving inferior olivary hypertrophy and cerebellar plasticity. 22,26 First, disruption of inhibitory cerebellar modulation of the ION leads to the development of somato-somatic gap junctions between neurons, generating periodic oscillations that are transmitted to the cerebellar cortex. The second mechanism would be a superimposed cerebellar "smoothing" of the output signal leading to smoother and less periodic eye movements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experimental data show that inferior olivary synchronization and modulation by the cerebellum play a role in OPT. 1 A literature search showed few reports of OPT from MS. An article that reviewed 171 publications on palatal myoclonus found 9 cases of MS among 287 cases. [2][3][4][5][6] However, on review many of these cases do not meet the current clinical criteria for diagnosis of MS. Neuroimaging or pathology was not available in any.…”
Section: Discussionmentioning
confidence: 99%
“…NMDA receptor antagonists such as memantine and alpha-2-delta calcium channel blocker such as gabapentin have been useful to treat the pendular nystagmus due to olivo-cerebellar dysfunction in the syndrome of ocular palatal tremor and that due of demyelinating disorders [80]. Contemporary studies have identified the role of ion channels in the pathogenesis of nystagmus and saccadic oscillations [80][81][82]. Therefore, it is critical to consider selective ion channel blockers as therapeutic options for the treatment of cerebellar nystagmus [81,83].…”
Section: Mechanicsmentioning
confidence: 99%